Evaluation of aqueous- pigmented rice extracts as bases for antioxidant drinks - Handayani, Adyati Putriekasari (2014)
Pigmented rice, which consists of black rice and red rice, are categorized as functional foods due to their antioxidant content, mainly contributed by anthocyanins for black rice and proanthocyanidins for red rice. However, as most of the antioxidant compounds in pigmented rice are hydrophilic, loss of antioxidants can occur during rice cooking in excess water. Therefore, the antioxidants in pigmented rice were extracted using hot water and the extracts were evaluated as bases for antioxidant drinks. The objectives of this study were to determine the optimum processing conditions for maximum DPPH radical scavenging activity, total flavonoid content, and total phenolic content in aqueous pigmented rice extracts; to evaluate the physical properties of the extracts; to compare the antioxidant capacities of the extracts with that of commercial fruit drinks; to evaluate the physical, antioxidant, and microbiological properties of the aqueous pigmented rice extracts during storage; to determine the effects of ingredients (citric acid, sodium benzoate, and sucrose) and carbonation on degradation kinetics of anthocyanins in aqueous black rice extract during storage. The optimization of the processing conditions for the aqueous pigmented rice extracts were determined using response surface methodology, and the optimized extracts were studied for their physical and antioxidant properties. The extracts were then stored for 12 weeks at room and refrigerated temperatures to evaluate their physical, microbiological, and antioxidant stability during storage. Lastly, high performance liquid chromatography (HPLC) was used to determine the anthocyanin degradation kinetics in aqueous black rice extract during storage. It was found that aqueous black rice extract had significantly higher (p<0.05) antioxidant power than aqueous red rice extract, and both rice extracts possessed significantly higher (p<0.05) antioxidant power compared to three commercial fruit drinks evaluated in this study. There was no significant difference between aqueous black and red rice extracts in terms of pH, viscosity, and total soluble solids. However, in terms of colour, aqueous black rice extract was significantly darker, more blue, and more red than aqueous red rice extract. The optimum hot water extraction conditions for black rice extract were water/rice (W/R) ratio of 20 ml/g at 92 oC for 40 minutes, while that for red rice extract were W/R ratio of 20 ml/g at 97 oC for 30 minutes. In terms of their storage stability, the variations in terms of antioxidant content and physical properties were observed more at storage temperature of 25 oC than at 4 oC. The extracts were able to be kept for 4 weeks at room temperature, while those kept at 4 oC remained microbiologically stable throughout 12 weeks of storage. It was also found that all four anthocyanin compounds in aqueous black rice extract, with and without added ingredients and carbonation, followed first-order reaction kinetic during storage. Cyanidin-3-rutinoside was the most stable anthocyanin compound, followed by peonidin-3-glucoside, cyanidin-3,5-diglucoside, and cyanidin-3-glucoside. Cyanidin-3-glucoside and peonidin-3-glucoside were stabilized by addition of 12% sucrose, while cyanidin-3,5-diglucoside and cyanidin-3-rutinoside were stabilized by addition of 0.3% citric acid. In conclusion, aqueous pigmented rice extracts have the potential of being the bases for antioxidant drinks.